Macroalgae in the Red Sea: A review of ecological, biotechnological, and regional implications - Taiba Alamoudi; Carlos M. Duarte (Journal of Applied Phycology, 2026)
Macroalgae are integral to marine ecosystems, contributing to primary production, biodiversity, nutrient cycling, and carbon capture. Despite their ecological and economic importance, the study of macroalgae in unique regions like the Red Sea, characterized by high temperatures, hypersalinity, and significant endemism, remains limited. Insights derived from this region offer information on resilience in the face of future climate change, informing broader global research on macroalgae. This review systematically synthesizes the state of knowledge by analysing 97 publications from 1994 to 2023 across four themes: molecular biology and ecology, ecophysiology, coral reef interactions, and blue biotechnology. Research efforts are geographically concentrated in the northern Red Sea and Gulf of Aqaba, leaving significant gaps in the western and southern regions, as well as the Gulf of Suez. We emphasize the multidisciplinary approach of macroalgal research and highlight knowledge gaps that persist in foundational taxonomy and in the quantification of macroalgal biomass, productivity, and ecosystem services like carbon sequestration. This review complements the extensive global literature in macroalgal science by consolidating regional findings on physiological adaptations, coral reef dynamics, and bioprospecting potential. We outline research needs prioritizing taxonomic resolution, basin-wide monitoring including mesophotic habitats, quantification of area, biomass, and production, the role of calcifying algae in reef accretion, contaminant baselines, and techno-economic pathways for sustainable cultivation to support conservation, innovation, and climate resilience in the Red Sea.